2019
DOI: 10.1016/j.aquaculture.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of fishpond effluent and production of microalgae for an oyster farm in an innovative recirculating integrated multi-trophic aquaculture system

Abstract: Integrated multi-trophic aquaculture (IMTA) systems are a promising solution for sustainable aquaculture combining nutrient recycling with increased biomass production. An innovative land-based recirculating aquaculture system (RAS) was studied in France for a 60-day experiment. It combined a European sea bass (Dicentrarchus labrax) RAS with two other production systems: high rate algal ponds (HRAP) with natural marine polyspecific algal assemblages, and oysters in separate open tanks. The objective was the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…Study 5b (Pagand et al, 2000) had a lower nitrogen removal rate than 5a because of the low light intensity during winter. For Studies 1 (Cahill et al, 2010) and 8 (Li et al, 2019), even though the nitrogen removal rate was 100%, which might indicate the efficiency of the algae, the nitrogen loading rates were low compared to other studies. For Studies 2 (Valeta and Verdegem, 2015) and 6 (Deviller et al, 2004), either light intensity or HRT was low, which caused the low nitrogen removal rate.…”
Section: Nitrogen Removal Rate In Algae Reactors In Rasmentioning
confidence: 56%
See 4 more Smart Citations
“…Study 5b (Pagand et al, 2000) had a lower nitrogen removal rate than 5a because of the low light intensity during winter. For Studies 1 (Cahill et al, 2010) and 8 (Li et al, 2019), even though the nitrogen removal rate was 100%, which might indicate the efficiency of the algae, the nitrogen loading rates were low compared to other studies. For Studies 2 (Valeta and Verdegem, 2015) and 6 (Deviller et al, 2004), either light intensity or HRT was low, which caused the low nitrogen removal rate.…”
Section: Nitrogen Removal Rate In Algae Reactors In Rasmentioning
confidence: 56%
“…When a comparison is made between macroalgae and microalgae (Figure 2), the macroalgae biomass (g algae m −2 algae reactor) was higher than the microalgae/periphyton biomass. Except for Study 8 (Li et al, 2019), a relatively high microalgal biomass was observed. This could be due to the HRAP technique used in that study that enhanced the growth of microalgae (Brune et al, 2003).…”
Section: Factors Affecting Nitrogen Removal Rates By Algae Algae Growmentioning
confidence: 90%
See 3 more Smart Citations